Extracts and Constituents of Rubus chingii with 1,1-Diphenyl-2-picrylhydrazyl (DPPH) Free Radical Scavenging Activity - Ding, Hsiou-Yu (Molecular Diversity Preservation International (MDPI), 2011)
The 1,1-diphenyl-2-picrylhydrazyl (DPPH) free radical scavenging activity of the fruits of Rubus chingii was studied in vitro. Ethanolic extract, ethyl acetate and n-butanol fractions from dried R. chingii fruits revealed strong DPPH free radical scavenging activity with IC(50) values of 17.9, 3.4 and 4.0 μg/mL, respectively. The ethyl acetate and n-butanol fractions were further purified by a combination of silica gel chromatography, Lobar RP-8 chromatography, and high-pressure liquid chromatography (HPLC). Nine compounds were isolated, where methyl (3-hydroxy-2-oxo-2,3-dihydroindol-3-yl)-acetate (2), vanillic acid (5), kaempferol (7), and tiliroside (9) showed stronger DPPH free radical scavenging activity than that of ascorbic acid (131.8 μM) with IC(50) values of 45.2, 34.9, 78.5, and 13.7 μM, respectively. In addition, rubusine (1) is a new compound discovered in the present study and methyl (3-hydroxy-2-oxo-2,3-dihydroindol-3-yl)-acetate (2), methyl dioxindole-3-acetate (3), and 2-oxo-1,2-dihydroquinoline-4-carboxylic acid (4) were isolated from the fruits for the first time.